Lyapunov-Krasovskii stability analysis of nonlinear integro-differential equation - Jackreece, Prebo (International Journal of Applied Mathematical Research, 2018)
The purpose of this paper is to develop a qualitative stability analysis of a class of nonlinear integro-differential equation within the framework of Lyapunov-Krasovskii. We show that the existence of a Lyapunov-Krasovskii functional is a necessary and sufficient condition for the uniform asymptotic stability of the nonlinear Volterra integro-differential equations.